2022
DOI: 10.3390/cells11091513
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Linolenic Acid Modulates T Cell Incorporation in a 3D Tissue-Engineered Psoriatic Skin Model

Abstract: Psoriasis is an autoimmune skin disease with an increased number of leukocytes infiltrating the dermal and epidermal compartments compared with normal skin. N-3 polyunsaturated fatty acids (n-3 PUFAs) are frequently used in the clinic in order to attenuate the symptoms of psoriasis. For psoriatic patients, a supplementation of the diet with alpha-linolenic acid (ALA) reduces the activation of T cell signaling pathways, leading to a significant reduction in inflammatory cytokine secretion. However, the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 72 publications
2
20
1
Order By: Relevance
“…Although the signalization involved in the pathogenesis of psoriasis has been investigated in recent years, much remains to be discovered. In this regard, our previous studies aimed to investigate the cellular and molecular mechanisms of psoriasis [ 7 , 8 , 10 , 13 , 33 , 34 , 35 , 36 ]. More recently, we developed a more complex biomaterial allowing the study of the interaction between skin and immune cells in a microenvironment that closely mimics that of the pathology [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the signalization involved in the pathogenesis of psoriasis has been investigated in recent years, much remains to be discovered. In this regard, our previous studies aimed to investigate the cellular and molecular mechanisms of psoriasis [ 7 , 8 , 10 , 13 , 33 , 34 , 35 , 36 ]. More recently, we developed a more complex biomaterial allowing the study of the interaction between skin and immune cells in a microenvironment that closely mimics that of the pathology [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ingredients that supply DHA and EPA n-3 PUFA are often the focus on contributing to the immunomodulatory effects rather than ALA due to cats having low delta-6 desaturase activity and lack of conversion of ALA to DPA and EPA. However, all three n-3 PUFAs play important roles in modulating the immune system through synthesis of prostaglandins and leukotrienes [ 32 ] and decrease inflammatory mediators released by T-cells [ 12 ]. Specifically, improving concentrations of ALA can improve skin moisture retention and result in skin and coat improvements in pets with poor coat quality [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanistic insight into ALA’s anti-inflammatory impact has been demonstrated in vitro by modulating NF-κB and mitogen-activated protein kinase [ 10 , 11 ]. More recently, ALA has been linked to decreasing pro-inflammatory mediators from T-cells, suggesting a direct effect of ALA on suppressing inflammation [ 12 ]. Furthermore, it has been observed that feeding flaxseed oil for 12 weeks to adult cats resulted in increased serum concentrations of ALA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, n-3 PUFAs seem to affect the immune system (34). Indeed, ALA was showed to affect T cell functions in the reconstructed psoriatic skin model, mainly by decreasing the production of inflammatory cytokines (200). The impact of n-3 PUFAs on the adaptive immunity have also been studied in other models.…”
Section: Effects Of Pufa and Bioactive Lipid Mediator Interventions I...mentioning
confidence: 99%